Apigenin oxidovanadium(IV) cation interactions : Synthesis, spectral, bovine serum albumin binding, antioxidant and anticancer studies - Martínez Medina, Juan José (2017)
Continuing and expanding our previous work on flavonoid oxidovanadium(IV) (VO) metal complexes as possible anti-cancer agents, the VOapigenin compound was synthesized and characterized. An “acetylacetone-like” coordination through the C=O and O moieties of the ligand to the metal center with one apigenin ligand per metal ion was assumed using different spectroscopies and elemental analysis as well as thermal measurements. The vibrational experimental spectrum of VOapigenin was supported by theoretical calculations. According to the structure of the flavonoid it exerted mild antioxidant properties that were enhanced by metal coordination. The compounds showed moderate anticancer activity on lung A549 and cervix HeLa cancer cell lines, displaying an incubation time dependent behavior. Cellular increase of reactive oxygen species (ROS) and glutathione depletion have been measured upon incubation with the compounds. These cell killing activities were reverted when natural antioxidants were incubated with the compounds and the addition of the antioxidant agent Nacetylcysteine generated depletion of the cellular ROS levels. Therefore, a stress oxidative mechanism of action has been assumed. Moreover, the compounds showed no toxicity against Artemia salina and were not mutagenic. Both apigenin and the complex could be transported and stored by bovine serum albumin with similar binding constants and mechanisms than other VOflavonoid complexes.